Novel targeted treatments in hairy cell leukemia and other hairy cell-like disorders - Maitre, Elsa; Paillassa, Jerome; Troussard, Xavier (Frontiers in Oncology, 2022)
In the category of mature B-cell neoplasms, splenic B-cell lymphoma and leukemia were clearly identified and include four distinct entities: hairy cell leukemia (HCL), splenic marginal zone lymphoma (SMZL), splenic diffuse red pulp lymphoma (SDRPL) and the new entity named splenic B-cell lymphoma/leukemia with prominent nucleoli (SBLPN). The BRAFV600E mutation is detected in nearly all HCL cases and offers a possibility of targeted therapy. BRAF inhibitors (BRAFi) represent effective and promising therapeutic approaches in patients with relapsed/refractory HCL. Vemurafenib and dabrafenib were assessed in clinical trials. The BRAFV600E mutation is missing in SDRPL and SBLPN: mitogen-activated protein kinase 1 (MAP2K1) mutations were found in 40% of SBLPN and VH4-34+ HCL patients, making possible to use MEK inhibitors (MEKi) such as trametinib, cobimetinib or bimetinib in monotherapy or associated with BRAFi. Other mutations may be associated and other signaling pathways involved, including the receptor B-cell signaling (BCR). cell cycle, epigenetic regulation and/or chromatin remodeling. In SDRPL, cyclin D3 (CCND3) mutations were found in 24% of patients, offering the possibility of using cell cycle inhibitors. Even if new emerging drugs, particularly those involved in the epigenetic regulation, have recently been added to the therapeutic armamentarium in HCL and HCL-like disorders, purine nucleoside analogs more and more associated with anti-CD20 monoclonal antibodies, are still used in the frontline setting. Thanks to the recent discoveries in genetics and signaling pathways in HCL and HCL-like disorders, new targeted therapies have been developed, have proven their efficacy and safety in several clinical trials and become essential in real life: BRAFi, MEKi, Bruton Tyrosine Kinase inhibitors (BTKi) and anti-CD22 immunotoxins. New other drugs emerged and have to be assessed in the future. In this article, we will discuss the main mutations identified in HCL and HCL-like disorders and the signaling pathways potentially involved in the pathogenesis of the different hairy cell disorders. We will discuss the results of the recent clinical trials, which will help us to propose an algorithm useful in clinical practice and we will highlight the different new drugs that may be used in the near future.